2014
DOI: 10.3390/v6114505
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Balance in Prion Diseases and Alzheimer’s Disease

Abstract: Prion diseases are transmissible and fatal neurodegenerative disorders of humans and animals. They are characterized by the accumulation of PrPSc, an aberrantly folded isoform of the cellular prion protein PrPC, in the brains of affected individuals. PrPC is a cell surface glycoprotein attached to the outer leaflet of the plasma membrane by a glycosyl-phosphatidyl-inositol (GPI) anchor. Specifically, it is associated with lipid rafts, membrane microdomains enriched in cholesterol and sphinoglipids. It has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 211 publications
(253 reference statements)
0
17
0
Order By: Relevance
“…In addition, the distribution of cholesterol between the exofacial leaflets and cytosolic leaflets of the PM is still debatable (see Section 2.5). From the patho-physiological standpoint, numerous studies have shown that cholesterol in the PM has crucial functions in cell signalling, endocytosis, bacterial/viral infection, cancer, angiogenesis, and Alzheimer’s disease [21,22,23,24,25,26]. Furthermore, cholesterol regulates the recycling pathway, which is consistent with enrichment of cholesterol in REs [5,27,28,29,30,31,32].…”
Section: Introductionmentioning
confidence: 68%
“…In addition, the distribution of cholesterol between the exofacial leaflets and cytosolic leaflets of the PM is still debatable (see Section 2.5). From the patho-physiological standpoint, numerous studies have shown that cholesterol in the PM has crucial functions in cell signalling, endocytosis, bacterial/viral infection, cancer, angiogenesis, and Alzheimer’s disease [21,22,23,24,25,26]. Furthermore, cholesterol regulates the recycling pathway, which is consistent with enrichment of cholesterol in REs [5,27,28,29,30,31,32].…”
Section: Introductionmentioning
confidence: 68%
“…This change persisted two weeks beyond the psychological stress exposure. Some studies suggest that cholesterol changes influence neurological disorders associated with protein aggregation like prion disease and Alzheimer’s disease-related dementia (Hannaoui et al, 2014). In light of this connection, our findings suggest that further investigations of the interactions between stress and HFHF consumption on cholesterol metabolism could shed new insight into the relationship between cardiovascular disease, MetS, cognitive decline, and dementia.…”
Section: Discussionmentioning
confidence: 99%
“…It was recently reported that HRS depletion affects cholesterol trafficking and leads to its accumulation in LE/ LY [53]. Interestingly, cholesterol was previously well characterized as a key factor involved in the conversion of PrP C into PrP Sc (for review [19]). Perturbation of cholesterol synthesis and trafficking prevents prion conversion or its degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Although PrP res (the PK-resistant form of PrP Sc ) is tightly associated with prion infectivity, PK-sensitive PrP Sc might be infectious as well [15]. The mechanisms that initiate the conversion of PrP C into its pathological isoform are still not fully understood but metabolism and trafficking of cholesterol were found both to play pivotal roles in prion conversion and/or degradation [16][17][18][19][20]. Both PrP C and PrP Sc isoforms are associated with lipid rafts/membrane microdomains (DRMs) enriched in cholesterol and sphingolipids [20][21][22] and preventing PrP C raft association or destabilization of rafts by cholesterol depletion blocks PrP C to PrP Sc conversion [19,23].…”
Section: Introductionmentioning
confidence: 99%